ECOTHEOLOGY IN ISLAMIC RELIGIOUS EDUCATION: A FRAMEWORK FOR DEVELOPING STUDENTS’ ECOLOGICAL RELIGIOUS CHARACTER - Wardatul Ilmiah; Fitri Hilmiyati; Ilzamudin Ma’mur; Umdatul Hasanah; Rasnam Rasyidi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
The increasingly complex global environmental crisis reflects not only technical failures in natural resource management but also a deeper crisis of human values and spirituality in relation to nature. In this context, ecotheology emerges as an integrative approach that connects theological, ethical, and ecological dimensions in addressing this crisis. This study aims to examine the role of ecotheology in Islamic Religious Education (PAI) as a theological foundation for shaping students’ religious character in higher education. This study employs a qualitative approach with a library research design, incorporating conceptual and thematic analysis of classical and contemporary Islamic scholarship, as well as recent articles from reputable Scopus-indexed journals (2023–2025). The findings reveal that ecotheology functions as both a normative and transformative framework in developing students’ religious character through the internalization of core Islamic values such as monotheism (tawhid), stewardship (khilafah), and trust (amanah). This process operates through four interconnected dimensions spiritual, moral, social, and ecological which collectively foster pro-environmental awareness and behavior. Furthermore, a transformative learning approach plays a crucial role in bridging the value–action gap, thereby strengthening sustainable value internalization. This study offers an integrative conceptual framework that positions ecotheology as a foundational paradigm in Islamic Religious Education for cultivating ecologically oriented religious character. Practically, it recommends the integration of ecotheological perspectives into the PAI curriculum through content enrichment, transformative pedagogical strategies, and eco-spirituality practices. These findings highlight ecotheology as a strategic approach to nurturing a generation that is religious, critical, and ecologically responsible in responding to the global environmental crisis.